Optimalisasi Distribusi BBM di Bengkulu Menggunakan Analytical Network Process and Metode CF-RS - Yasin, Muhamad; Putra, Rama Dani Eka; Fitri, Tessa Zulenia; Foci, Nia Arfina; Munanda, M. Arif (Greeners: Journal of Green Engineering for Sustainability, 2025)
Fuel scarcity in Bengkulu Province has occurred in the last few days. In fact, prices at the retail level have soared to Rp30,000 per liter. This study aims to provide solutions to the fuel distribution problems in Bengkulu that have been explained previously and provide optimal solutions using the Analytical Network Process Method and the Cluster First Route Second (CFRS) Method. so that the determination of the closest route is Tank Truck 11 with the route Lubuklinggau Fuel Terminal - Gas Station 6 Bengkulu City - Lubuklinggau Fuel Terminal with a distance of 234 KM and the farthest route is Lubuklinggau Fuel Terminal - Gas Station 11 - Gas Station 3 - Lubuklinggau Fuel Terminal.